Are 1, 4‐ and 1, 5‐Disubstituted 1, 2, 3‐Triazoles Good Pharmacophoric Groups?. Issue 11 (30th July 2014) - Massarotti, Alberto; Aprile, Silvio; Mercalli, Valentina; Del Grosso, Erika; Grosa, Giorgio; Sorba, Giovanni; Tron, Gian Cesare
Abstract Over the last decade, 1, 2, 3‐triazoles have received increasing attention in medicinal chemistry thanks to the discovery of the highly useful and widely applicable 1, 3‐dipolar cycloaddition reaction between azides and alkynes (click chemistry) catalyzed by copper salts and ruthenium complexes. After a decade of medicinal chemistry research on 1, 2, 3‐triazoles, we feel that the time is ripe to demonstrate the real ability of this heterocycle to participate in important and pivotal binding interactions with biological targets while maintaining a good pharmacokinetic profile. In this study, we retrieved and analyzed X‐ray crystal structures of complexes between 1, 2, 3‐triazoles and either proteins or DNA to understand the pharmacophoric role of the triazole. Furthermore, the metabolic stability, the capacity to inhibit cytochromes, and the contribution of 1, 2, 3‐triazoles to the overall aqueous solubility of compounds containing them have been analyzed. This information should furnish fresh insight for medicinal chemists in the design of novel bioactive molecules that contain the triazole nucleus.